Overview of axillary dermatoses: case series in a tertiary care institution - A., Ramesh; V., Sampath; P., Kasiviswanathan; D., Rajan Babu (International Journal of Research in Dermatology, 2019)
Background: Axillary dermatoses are common skin disorders in the general population. The objective was to find out the age and sex incidence of various skin dermatoses in the axillae in patients attending the outpatient department of dermatology and to find out the various clinical types of axillary dermatoses. Methods: It was a prospective observational study carried out in a tertiary care hospital, Chennai, Tamil Nadu, India. Patients with skin lesions confined only to the axillae were included in the study thorough history, clinical examination, routine and special investigations like skin biopsy. Results: Out of 76 patients of our study group, the age ranged from 40 days to 59 years; 55 were males, 21 were females and six children with male to female ratio of 1:1. Most commonly affected age group was 30-40 years (25%). Most common axillary dermatoses in this study was tinea axillaris (21.05 %), followed by pityriasis versicolor (19.73%), erythrasma (9.21%), acanthosis nigricans (6.57%), etc. Conclusions: This study highlights awareness and the increasing trend of axillary dermatoses with predominance of male predilection. Early detection and treatment of lesions are crucial to decrease the functional and cosmetic disfigurements especially hidradenitis suppurativa. This study highlights the importance of improving awareness among the general population especially the rampant use of cosmetics. Skin biopsy for diagnosis of neurodegenerative disorder, dermatologists plays a crucial role.